Debris and safe near railroad tracks - Gordon, John C. (photographer):::Creator::::::::::::
A pile of debris, possibly following a fire. A safe with charred contents sits in the center. Its door has come off its hinges. Atop the safe are the remnants of what once might have been an adding machine or a typewriter. In the background are utility poles and railroad boxcars.